THE EFFECT OF GAMIFICATION AND ONLINE CUSTOMER REVIEW ON PURCHASING DECISION THROUGH E-SERVICE QUALITY ON THE LAZADA E-COMMERCE PLATFORM - Muhammad Rasyid Ridlo; Rahmadi Rahmadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Indonesia's e-commerce industry is expanding quickly, which has increased rivalry among marketplace platforms, requiring strategies beyond price orientation to sustain consumer engagement and purchasing decisions. Despite growing interest in gamification and online customer reviews as digital marketing tools, empirical evidence on their simultaneous influence on purchasing decisions particularly through the mediating function of e-service quality on the Lazada platform remains scarce in regional Indonesian contexts. This research attempts to examine the effect of gamification and online customer reviews on purchasing decisions with e-service quality as a mediating variable among Lazada users in Cirebon City. A quantitative approach using PLS-SEM was employed with 165 respondents selected through purposive sampling. The results confirm that gamification (β = 0.231, p = 0.001) and online customer reviews (β = 0.513, p = 0.000) have a positive and significant effect on purchasing decisions, with the model demonstrating strong predictive power (R² = 0.684). Most importantly, e-service quality was proven to partially mediate the interaction between gamification and purchasing decisions (indirect effect = 0.086, p = 0.007), in addition to between online customer reviews and purchasing decisions (indirect effect = 0.062, p = 0.018), confirming its critical bridging role in driving consumer purchasing behavior on e-commerce platforms.